Examining the Relationship between Production, Trade and Consumption Using Hierarchical Analysis Methods - Timiryanova, Venera M. (Economy of Regions, 2021)
Reproduction is a continuous process of production, distribution and consumption of products in the hierarchy of economic space. Simultaneously, local production depends on both domestic demand and wholesale promotion of products to international markets. The study determines the influence of the wholesale, defining the distribution and trade stages, on the shipping volume, characterising the production stage. The research aims to correlate territorial hierarchy (country → region → municipality) with the reproduction sequence (production → distribution/trade → consumption). Additionally, it attempts to decompose the observed variation of the shipping volume in accordance with the hierarchy of economic space using the hierarchical linear modelling (HLM). The differences between municipalities are analysed in the context of two territorial levels: municipal (population income, determining consumption) and regional (wholesale trade, characterising the distribution) ones. The research examined the data for 2017 on 331 municipalities of 7 constituent entities of the Russian Federation. The study results show that hierarchical analysis methods can be used to analyse the relationship between production, distribution and consumption. In the considered territory, the shipping volume was mostly influenced by domestic consumption and to a much lesser extent wholesale trade. The application of hierarchical analysis methods enhances the analysis of reproduction. Moreover, it allows the government to create favourable conditions for implementing the programmes of infrastructure development and assessing supply capabilities of trade and production enterprises.